Ex-wife - Parrott, Ursula, 1899-1957 (McNally Editions (Series), 2023)
"It’s 1924, and Peter and Patricia have what looks to be a very modern marriage. Both drink. Both smoke. Both work, Patricia as a head copywriter at a major department store. When it comes to sex with other people, both believe in “the honesty policy.” Until they don't. Or, at least, until Peter doesn’t—and a shell-shocked, lovesick Patricia finds herself starting out all over again, but this time around as a different kind of single woman: the ex-wife. An instant bestseller when it was published anonymously in 1929, Ex-Wife captures the speakeasies, night clubs, and parties that defined Jazz Age New York—alongside the morning-after aspirin and calisthenics, the lunch-hour visits to the gym, the girltalk, and the freedoms and anguish of solitude. It also casts a cool eye on the bedrooms and the doctors’ offices where, despite rising hemlines, the men still call the shots. The result is a unique view of what its author Ursula Parrott called “the era of the one-night stand.” - from publisher website